2019
DOI: 10.1097/inf.0000000000002198
|View full text |Cite
|
Sign up to set email alerts
|

Two Randomized Trials of the Effect of the Russian Strain of Bacillus Calmette-Guérin Alone or With Oral Polio Vaccine on Neonatal Mortality in Infants Weighing <2000 g in India

Abstract: List of abbreviations AFR. african region AMR. antimicrobial resistances BCG. bacillus calmette-guérin BUD. buruli ulcera disease CFU. colony forming units DHS. demographic health surveys DRDR. drug resistance determining regions DSJI. disposable-syringe jet injectors DST. drug susceptibility testing EID. early infant HIV diagnosis EMR. eastern mediterranean region EUR. european region G2D. grade-2 disabilities GLP. global leprosy programm GTB. global TB programme HBsAg. hepatitis B surface antigen HCWs. healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
54
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(54 citation statements)
references
References 81 publications
0
54
0
Order By: Relevance
“…Most trends noted in the development of the concept of the NSEs of MV starting from 1979 turned out to be consistent in later studies. Several RCTs of MV, BCG and OPV have found strong beneficial NSEs (41,55,63), though the results have not been universally consistent (44,79).…”
Section: Implications and Conclusionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most trends noted in the development of the concept of the NSEs of MV starting from 1979 turned out to be consistent in later studies. Several RCTs of MV, BCG and OPV have found strong beneficial NSEs (41,55,63), though the results have not been universally consistent (44,79).…”
Section: Implications and Conclusionmentioning
confidence: 99%
“…BCG strongly reduced the risk of neonatal sepsis (43). Two subsequent RCTs in India using BCG-Russia found no benefit among extreme LBW children (<2.000 kg) (44). This may relate to strain of BCG, as several studies have found the BCG-Denmark is much better in inducing a BCG-scar but also provide more adverse events than BCG-Russia (45).…”
Section: Non-specific Effects Of Bcg Vaccinementioning
confidence: 99%
See 1 more Smart Citation
“…Most studies assessing the effect of BCG on all-cause mortality compared BCG-vaccinated children with unvaccinated children6 23 24 and randomised trials of BCG-Denmark have found beneficial effects in the neonatal period 8. It should be noted that two recent trials testing the effect of BCG-Russia in India found no effect;25 the different results may be related to different BCG strains 25 26. A previous study from the 1990s in Guinea-Bissau found that BCG was associated with stronger beneficial effects if provided in the first week of life 27.…”
Section: Discussionmentioning
confidence: 99%
“…The beneficial NSEs of BCG are of variable magnitude 4 38. A number of potential explanations are in play, including differences in BCG strain,39–41 batch variation strains,42 the enhancing effect of parental priming with BCG,43 44 genetic polymorphisms45 46 and different underlying aetiologies of neonatal disease and death.…”
Section: Discussionmentioning
confidence: 99%